The Reliability of Fishman and Nolla Methods in Prediction of Chronological Age of Yemeni Children - Alqadi, Maktoom Abdulrakeeb; Abuaffan, Amal H (Brazilian Dental Science, 2020)
Objective: This cross-sectional school based study aimed to assess the reliability of Fishman and Nolla methods in predicting the chronological age for Yemeni children. Material and Methods: Orthopantomographs and left handwrist radiographs were taken for 358 Yemeni children (193 boys and 165 girls) 8 - 16 years. Skeletal age estimated by Fishman method and dental age estimated by Nolla method were compared to chronological age using SPSS version 21, statistical significance was predetermined at P < 0.05 , using Intraclass Correlation Coefficient- ICC and Wilcoxon signed rank test. Results: The mean chronological, skeletal and dental ages were 12.00 ± 2.25 years, 12.39 ± 1.65 years and 11.32 ± 2.65 years, respectively. Intraclass correlation coefficient showed strong correlation between chronological age and skeletal and dental ages. Wilcoxon test showed Fishman method significantly underestimated the chronological age by 0.44 ± 1.26 years in boys and non-significantly underestimated the chronological age by 0.02 ± 1.08 years in girls. Nolla method significantly underestimated the chronological age by 0.59 ± 1.28 years in boys and 0.78 ± 1.21 years in girls. Conclusions: Chronological age of Yemeni children is highly correlated to skeletal age estimated by Fishman method and dental age estimated by Nolla method. However, the two methods underestimate the chronological age of Yemeni children.KeywordsAge determination by teeth; Orthodontics; Age determination by skeleton; Forensic dentistry; Yemen.